PENERAPAN APLIKASI QUICK RESPONSE DALAM MELAYANI PENGADUAN MASYARAKAT BERBASIS WEB DAN SMS GATEWAY - Swara, Ganda Yoga (STKIP PGRI Sumatera Barat, 2020)
Quick Response application is an application designed to meet the needs of the community. This application is a forum for the public to convey to the relevant Regional Government. Types of complaints that the public can convey are complaints, questions, information and suggestions / proposals related to the topic of the complaint, namely about education, agriculture, health, population, food crop agriculture, road infrastructure, tourism, youth, sports, disaster management, and trade and market. The application designed in this research is web based and SMS Gateway. In its design, this website is made using the PHP programming language and also uses the MYSQL database. For SMS Gateway, it was designed using Gammu application. By using the web, people can send their complaints online. Even the public can also ask for their complaints with the SMS service. With this application, it is also expected to be able to facilitate the local government, as well as related parties involved and provide responses from public complaints that can be accounted for.